Differential Wall Rock Movements Associated With Rock Bursts, Lucky Friday Mine, Coeur d'Alene Mining District, Idaho, USA - B. G. White; J. K. Whyatt (The National Institute for Occupational Safety and Health (NIOSH))
Various methods of monitoring slip movements on bedding planes, as well as examination of rock burst damage in stopes, suggests that rock bursts in the Lucky Friday Mine are closely associated with these movements. Slip displacements along bedding simultaneously reduce the physical dimensions of stopes and increase compressive stress along stope margins. Such changes, in turn, contribute directly to rock bursts and the sudden failure of volumes of rock and cemented sandfill surrounding stopes. The distribution of seismicity and several mining-induced and premining structures resemble those described in South African gold mines. These suggest fundamental similarities in seismic sources and mechanisms of rock burst damage.